Integration practices - Svraka, Bernadett; Lo Bello, Maya J.; Márkus, Éva (Gyermeknevelés Tudományos Folyóirat, 2022)
The pedagogical practice of acceptance paves the way to integrating those disadvantageous children who can only live their daily lives with support and would experience a learning process full of failures without the proper aid. Societal expectations and social integration can only meet successfully when the spirit of educational institutions and the attitude of teachers demonstrate an accepting attitude. The structure of the institution must furthermore undergo a transformation. When good practices are included in institutional regulatory documents and efforts are made to comply with them, i.e., the institution adapts to the individual needs of the child, then inclusion can be said to occur. Ensuring the conditions necessary for inclusion is a major challenge for the teaching community. Many creative initiatives launched for the purpose of implementing integration demonstrate that the harmonious cooperation of teachers, parents, and children is essential in the process. An example of such an initiative can be found in the second phase of our sensitising series.